Top management commitment, corporate social responsibility and green human resource management - Yusliza, M.-Y.; Nurul Aimi, Norazmi; Jabbour, Charbel Jose Chiappetta; Fernando, Yudi; Fawehinmi, Olawole; Seles, Bruno Michel Roman Pais (Emerald, 2019)
Purpose The purpose of this paper is to analyse the relationship between top management commitment, corporate social responsibility (CSR) and green human resource management (GHRM).